LITERASI PENYAKIT DEGENERATIF UNTUK MENGELOLA DAN MENINGKATKAN KUALITAS HIDUP PENDERITA HIPERTENSI PADA LANSIA DI DESA PANAIKANG, KECAMATAN PATALASSANG, KABUPATEN GOWA, SULAWESI SELATAN - Azniah Syam; Indra Dewi; Nur Khalid (Bajang Institute, 2023)
As the older population grows, the need for home care services will rise. Elderly independence is different. Chronically ill seniors need independence to manage their illness and achieve a high quality of life. Patalassang Village in Gowa, South Sulawesi, has a high proportion of old individuals with at least one chronic disease issue, threatening the community's quality of life. Increase independence to improve life quality. This activity helps the elderly manage chronic conditions, especially hypertension. Two-hour participative model for activity implementation. The activity aims to raise senior knowledge of primary hypertension by at least 45%. Based on the five evaluation indicators, 80% of hypertension was understood, so output indicators 36% above the target. Panaikang Village, Patalassang District, Gowa Regency's older community should be enthusiastic about sustaining quality of life, especially managing and improving health against chronic diseases.